RETRACTED: Circular RNA hsa_circ_0013958 Functions as an Oncogenic Gene Through Modulating miR-532-3p/WEE1 Axis in Hepatocellular Carcinoma - Ma, Tao; Ma, Yue; Du, Yongjun; Wei, Zhongheng; Wang, Jianchu; Jun, Yufu; Xiao, Fenqiang (Frontiers in Oncology, 2021)
Background: circ0013958 was identified as a biomarker, which can be used for the diagnosis and screening of lung cancer. However, the role of circ0013958 in hepatocellular carcinoma (HCC) remains unclear. Methods: In our study, quantitative real-time polymerase chain reaction was performed to determine the levels of circ0013958 in HCC tissues and cell lines. EdU, CCK-8, transwell, flow cytometry and tumorigenesis assays were applied to assess the functions of circ0013958 in HCC in vitro and in vivo. Western blot assay was to detect the expression of WEE1. Luciferase reporter assay, bioinformatics analysis and rescue experiments were used to examine the interaction among circ0013958, miR-532-3p and WEE1. Results: It revealed that circ0013958 was significantly up-regulated in HCC, which was positively correlated with poor prognosis of HCC patients. Circ0013958 promoted HCC cell proliferation and invasion, inhibited cell apoptosis in vitro, and promoted tumorigenesis in vivo. Circ0013958 acted as a miR-532-3p sponge to regulate WEE1 expression, thus promoting the progression of HCC. Conclusions: Circ0013958 promotes HCC progression through miR-532-3p/WEE1 axis. Circ0013958 may serve as a potential diagnostic biomarker and therapeutic target of HCC. Keyword: hepatocellular carcinoma, circ0013958, miR-532-3p, WEE1, ceRNA